Project Management Strategies and Optimization of Construction Supply Chain in Rwanda’s Construction Projects - Tuyishime, Enock; Njoroge, Naomi (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: This study explored management strategies and their influence on optimizing the construction supply chain in Rwanda, focusing on the Amahoro Stadium project. The specific objectives included assessing the impact of logistics management, technology integration. Methodology: A mixed-methods approach with a descriptive survey design was used, targeting 128 individuals and entities involved in the construction supply chain of Amahoro Stadium. The sample size of 97 respondents was determined using the Granular formula. Data were collected through questionnaires and interviews, combining both quantitative and qualitative insights. Findings: The study revealed that logistics management, technology integration, and customer management all have significant positive relationships with the optimization of the construction supply chain in Rwanda. Key findings included a strong agreement among respondents that effective transportation (43.2%), inventory control (48.4%), and customer feedback (83.6%) influence supply chain optimization. The correlation analysis showed that 87.6% of the variation in construction supply chain optimization can be explained by these three independent variables. The study concluded that a comprehensive strategy involving logistics management, technology integration, and customer engagement is essential for optimizing construction supply chains in Rwanda. Unique Contribution to Theory, Practice and Policy: Recommendations include investing in logistics training, adopting advanced technologies, and fostering customer relationships to improve satisfaction and project outcomes. Further research into the long-term impacts of these strategies on supply chain optimization and sustainability was also suggested.